2007
DOI: 10.1002/cem.1082
|View full text |Cite
|
Sign up to set email alerts
|

Combining classification and regression approaches for the quantification of highly overlapping capillary electrophoresis peaks by using evolutionary sigmoidal and product unit neural networks

Abstract: This is a study of the potential of neural networks built by using different transfer functions (sigmoidal, product and sigmoidal-product units) designed by an evolutionary algorithm to quantify highly overlapping electrophoretic peaks. To test this approach, two aminoglycoside antibiotics, amikacin and paramomycin, were quantified from samples containing either only one component or mixtures of them though capillary zone electrophoresis (CZE) with laser-induced fluorescence (LIF) detection. The three models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Further details of this algorithm could be found in [28]. The parameters of the evolutionary algorithm are shown in Table 6, whereas, the remaining values were obtained from [29].…”
Section: Experimental Datamentioning
confidence: 99%
“…Further details of this algorithm could be found in [28]. The parameters of the evolutionary algorithm are shown in Table 6, whereas, the remaining values were obtained from [29].…”
Section: Experimental Datamentioning
confidence: 99%
“…Finally, the minimum number of hidden nodes, the maximum number of hidden nodes in the initialisation phase and the maximum number of hidden nodes in the whole evolutionary process were set at 1, 2, and 4, respectively. All these values were selected following a 5-fold cross-validation on the training set, and the remaining values were obtained from Hervás-Martínez et al [42].…”
Section: Experimental Designmentioning
confidence: 99%
“…This study showed the potential of different artificial neural networks for the quantitation of overlapped peaks to predict the contribution of each component to the overall analytical signal. This allows an important reduction in analysis time since it avoids time consumption by finding optimal conditions for the suitable CZE resolution 54.…”
Section: Aminoglycosidesmentioning
confidence: 99%